2019
DOI: 10.4093/dmj.2018.0123
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Selenium Level and the Presence of Diabetes Mellitus: A Meta-Analysis of Observational Studies

Abstract: Background Epidemiological studies have suggested an association between selenium (Se) and diabetes mellitus (DM). However, different studies have reported conflicting results. Therefore, we performed a comprehensive meta-analysis to clarify the impact of Se on DM. Methods We searched the PubMed database for studies on the association between Se and DM from inception to June 2018. Results Twenty articles evaluating 47,930 participants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 49 publications
1
40
1
1
Order By: Relevance
“…Significant association was shown among studies that used blood, diet, and urine as specimens for Se level detection but not in studies that used nails as a sample for Se measurement. Sensitivity analysis was conducted in addition to the trim and fill analysis to account for the heterogeneity and the publication bias, yet the results were consistent upon all adjustments [18]. Another non-linear dose–response analysis confirmed that both levels below and above the physiological range are potential risk factors for diabetes which is consistent with other review articles that suggested a U-shaped relationship between Se and diabetes.…”
Section: Selenium In Health and Disease: The Importance Of A Balansupporting
confidence: 67%
See 3 more Smart Citations
“…Significant association was shown among studies that used blood, diet, and urine as specimens for Se level detection but not in studies that used nails as a sample for Se measurement. Sensitivity analysis was conducted in addition to the trim and fill analysis to account for the heterogeneity and the publication bias, yet the results were consistent upon all adjustments [18]. Another non-linear dose–response analysis confirmed that both levels below and above the physiological range are potential risk factors for diabetes which is consistent with other review articles that suggested a U-shaped relationship between Se and diabetes.…”
Section: Selenium In Health and Disease: The Importance Of A Balansupporting
confidence: 67%
“…Se depending on its status has been reported to play crucial roles in normal physiology or contribute the pathophysiology of various diseases. Se has antioxidant and anti-inflammatory actions and therefore various studies have assessed the impact of Se status on conditions characterized by inflammation and oxidative stress including, neurodegenerative diseases, diabetes, cancer, and cardiovascular disorders [18].…”
Section: Selenium In Health and Disease: The Importance Of A Balanmentioning
confidence: 99%
See 2 more Smart Citations
“…As a chronic hyperglycaemia can cause a substantial increase of reactive oxygen species (ROS) and oxidative stress, leading to diabetes‐related complications and a decreased Se level , it was hypothesised that, in patients diagnosed with T2DM, Se supplementation may be beneficial. However, a number of studies indicate that it may act adversely on glucose homeostasis and insulin sensitivity and even increase the risk of T2DM . This can be partially explained by the impact of Se on selenoproteins and insulin signalling .…”
Section: Introductionmentioning
confidence: 99%